Penanganan Kredit sebagai Kebijakan Countercyclical Dampak Penyebara Corona Virus Disease 2019 Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor ll/POJK.03/2020 di PT BPR Saptacristy Ut ama - Kadek Dani Arditha Perrnana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2021)
The spread and growth of the Corona Virus in Indonesia directly and indirectly affect the performance and the capacity of micro, small, as well as medium business debtors. Therefore, it may undermine bank performance and financial system stability, thereby affecting economic growth. Based on these considerations, the Financial Services Authority (Otoritas Jasa Keuangan) issued the Financial Services Authority regulation number 11 /POJK/03/2020 which regard National Economic Stimulus as a Countercyclical Policy for the impact of Corona Virus Disease 2019. The purpose of this research is to find out how the Financial Services Authority's policies are in dealing with bad credit due to Covid-19. The research method that carried out in this scientific paper is the empirical method, namely legal research based on actual conditions in the field. The results of this research are the things that have not been regulated in the credit agreement can be changed and or added by using an additional agreement or addendum. In the Financial Services Authority Implementation Regulation No. l l/POJK.03/2020, the Financial Services Authority requires every bank to formulate guidelines to designate debtor's affectively the spread of Coronavirus Disease 2019. Each bank will have different policies for handling the credit of its debtor's.